1987
DOI: 10.1080/01688638708405353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of information-processing speed and neuropsychological functioning in patients with myotonic dystrophy

Abstract: Patients with myotonic dystrophy (MD) were compared to a control group, matched to the patients in important demographic variables including IQ, on the Sternberg Memory Scanning procedure, to investigate the hypothesis of a selective change in speed of information processing in MD patients. The neuropsychological functioning of these MD patients was also compared to normative data to provide a descriptive picture of their abilities; these results were correlated to the factors of age of onset and duration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…In more recent studies, however, the intellectual level has been at least slightly below the normal level [2][3][4][5][6][7][8]. The relative proportion of DM patients with mental retardation has usually varied from 10 to 24% [3,5,[6][7][8], but Cencori et al [9] found significant global intellectual impairment in 50% of the patients (using the Raven's Colored Progressive Matrices as a test). In two studies no patient scored in the mentally retarded range [2,4], The present material includes about 10% of the Finnish DM patients, and 50% of the esti mated number of DM patients living in this area.…”
Section: Discussionmentioning
confidence: 99%
“…In more recent studies, however, the intellectual level has been at least slightly below the normal level [2][3][4][5][6][7][8]. The relative proportion of DM patients with mental retardation has usually varied from 10 to 24% [3,5,[6][7][8], but Cencori et al [9] found significant global intellectual impairment in 50% of the patients (using the Raven's Colored Progressive Matrices as a test). In two studies no patient scored in the mentally retarded range [2,4], The present material includes about 10% of the Finnish DM patients, and 50% of the esti mated number of DM patients living in this area.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that degeneration of the neuronal architecture of the entorhinal cortex destroys a large functional part of hippocampal input and output, resulting in the memory and cognitive deficits associated with Alzheimer's disease (Braak et al, 1993). It is possible that more discrete lesions in the same cells may result in the less drastic abnormalities in memory functions that have been noted in patients with myotonic dystrophy, including nonprogressive abnormalities in immediate recall, abstraction, spatial manipulation, and attention (Harper, 1975(Harper, , 1989Woodward et al, 1982;Bird et al, 1983;Portwood et al, 1984Portwood et al, , 1986Stuss et al, 1987;Censori et al, 1990;Censori et al, 1994;Miller, 1992;Tuikka et al, 1993;Abe et al, 1994;Palmer et al, 1994).…”
Section: Discussionmentioning
confidence: 94%
“…There is currently little understanding of the role of DMPK in the CNS and of the pathological effects of abnormally expressed kinase upon these functions. Any plausible explanation of the physiologic function of DMPK in the CNS would have to account for the developmentally variable manifestations of myotonic dystrophy and the involvement, in the ''adult'' form, of apparently discrete and functionally separate regions of the CNS (Rosman and Kakulas, 1966;Rosman and Rebeiz, 1967;Harper, 1975Harper, , 1989Hansotia and Frens, 1981;Bird et al, 1983;Portwood et al, 1984Portwood et al, , 1986Stuss et al, 1987;Miller, 1992;Abe et al, 1994).…”
mentioning
confidence: 97%
“…Portwood, Wicks, Lieberman, and Fowler (1984) noted no significant difference between MD patients' WAJS-R Verbal versus Performance IQs. Furthermore, when comparing MD patients to IQ matched controls, Stuss et al (1987) observed no significant differences in most of a battery of tests, with the exception of finger tapping speed and unexpectedly superior verbal paired associate performance among MD patients relative to controls.…”
mentioning
confidence: 78%
“…In addition, some investigators have found low verbal fluency performance among MD patients (Censori et al, 1990;Huber et al, 1989;Sinforiani et al, 1991). In contrast, however, other investigators reported no significant deficits among MD patients on card sorting or verbal fluency tasks (Malloy et al, 1990;Stuss et al, 1987).…”
mentioning
confidence: 90%